2013
DOI: 10.1152/ajpheart.00070.2013
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ventricular transient outward K+ current by acidosis and its effects on excitation-contraction coupling

Abstract: Saegusa N, Garg V, Spitzer KW. Modulation of ventricular transient outward K ϩ current by acidosis and its effects on excitation-contraction coupling. Am J Physiol Heart Circ Physiol 304: H1680 -H1696, 2013. First published April 12, 2013 doi:10.1152/ajpheart.00070.2013.-The contribution of transient outward current (Ito) to changes in ventricular action potential (AP) repolarization induced by acidosis is unresolved, as is the indirect effect of these changes on calcium handling. To address this issue we mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Acidosis reduces myocardial contractility via alterations in intracellular calcium handling and contractile protein sensitivity to calcium. 37 Furthermore, acidosis affects b-adrenergic−receptor expression, contributing to reduced contractility. 38 To assess the physiologic impact of different types of acidemia on cardiac function and systemic hemodynamics, mechanically ventilated pigs with respiratory and metabolic acidosis were studied.…”
Section: Metabolic Acidosismentioning
confidence: 99%
“…Acidosis reduces myocardial contractility via alterations in intracellular calcium handling and contractile protein sensitivity to calcium. 37 Furthermore, acidosis affects b-adrenergic−receptor expression, contributing to reduced contractility. 38 To assess the physiologic impact of different types of acidemia on cardiac function and systemic hemodynamics, mechanically ventilated pigs with respiratory and metabolic acidosis were studied.…”
Section: Metabolic Acidosismentioning
confidence: 99%
“…Interestingly, Saegusa et al (2013) observed differential effects of intracellular and extracellular acidification on the action potential duration: intracellular pH reduction resulted in action potential prolongation while extracellular acidosis reduced action potential duration (Saegusa et al, 2013). These authors found that intracellular acidification reduced the transient outward current I(t.o.)…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular acidification shifted I(t.o.) inactivation toward less negative potentials (Saegusa et al, 2013). Another important effect is that regarding the ATP-inhibited K + current I(K.ATP) (ATP-sensitive potassium current) it was described that hypoxia and ATP depletion can activate this current leading to action potential shortening (Wilde et al, 1990) and that -on the other hand-extracellular H + ions can inhibit I(K.ATP) (Moncada et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is to be noted that any change in AP waveform affects I CaL . Saegusa et al [85] performed experiments on rabbit ventricular myocytes and showed that intracellular acidosis strongly decreased I to , increasing AP plateau and decreasing peak I CaL . Their AP voltage clamp approach allowed them to determine that intracellular pH-induced changes in AP waveform (plateau elevation) per se, reduced I CaL , without the complicating effects of intracellular acidosis.…”
Section: Discussionmentioning
confidence: 99%